218k views
5 votes
Which function in vertex form is equivalent to f(x) = 4 + x2 – 2x?

f(x) = (x – 1)2 + 3
f(x) = (x – 1)2 + 5
f(x) = (x + 1)2 + 3
f(x) = (x + 1)2 + 5

2 Answers

3 votes

Answer:

A:

f(x) = (x – 1)2 + 3

User Jordeu
by
6.8k points
0 votes
To express a function of the form
f(x)= x^(2) +bx+c in vertex form
f(x)=a(x-h)^2+k where (h,k) is the vertex of the parabola, we need to find the vertex first.
To find the vertex we are going to use the vertex formula:
h= (-b)/(2a), and
k will be the function evaluated at
h.
We can infer from our function that
a=1 and
b=-2. So lets find
h:

h= (-b)/(2a)

h= (-(-2))/(2(1))

h= (2)/(2)

h=1
Now that we have
h, we can evaluate the function at 1 to find
k:

f(x)=4+ x^(2) -2x

f(1)=4+(1)^2-2(1)

f(1)=4+1-2

f(1)=3

We have the vertex (1,3) of our parabola, so we can use its vertex form:

f(x)=a(x-h)^2+k

f(x)=1(x-1)^2+3

f(x)=(x-1)^2+3

We can conclude that the vertex for of our parabola is f(x) = (x + 1)2 + 3.
User Kyle Pfromer
by
5.8k points